Relasi antara Teologi dengan Filsafat Apologetika dan Penginjilan - Alpina Siska; Calissta Audrie Salsabila; Feronika Sitriel Yaas; Niko Niko; Kusnadi Kusnadi; Sarmauli Sarmauli (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
This study explores the intricate relationship between theology and philosophy within the framework of Christian apologetics and evangelism, aiming to understand and communicate faith in both rational and contextual ways. Theology, grounded in divine revelation, serves as the foundational source of truth, while philosophy offers critical and analytical tools to interpret, clarify, and logically articulate theological doctrines. Apologetics operates as a dynamic bridge between these disciplines, integrating rational discourse, ethical reflection, and spiritual conviction to defend and proclaim the Gospel effectively in an increasingly pluralistic and intellectually diverse society. This research employs a library-based qualitative approach utilizing descriptive and analytical methods to examine theological and philosophical literature from various academic perspectives. The findings demonstrate that theology, philosophy, and apologetics form an interdependent and complementary framework that not only strengthens evangelism but also enables Christians to present the Gospel message rationally, contextually, and meaningfully amidst the contemporary challenges of faith, culture, and reason.